Three+two Raman lidar system configuration for space-borne active remote sensing system validation over Athens, Greece, in the frame of the EARLINET-ASOS and ESA-CALIPSO projects - Papayannis, Alexandros D.; Amiridis, Vassilis; Mamouri, Rodanthi-Elisavet (My University, 2009)
Routine lidar measurements of the aerosol vertical distribution have been performed over Athens, Greece using a multiwavelength (355-387-407-532-607-1064 nm) Raman lidar system, since 2006 in the frame of the EARLINET-ASOS (2006-2011) project. Additionally, since June 2006, correlative measurements for CALIOP space-borne lidar are performed. The aim of these measurements is to provide validation profiles for the CALIOP instrument in the lower and middle troposphere (0.5-8 km) in terms of the aerosol backscatter coefficients at 532 nm and 1064 nm, the color ratio (532/1064 nm) and the depolarization ratio at 532 nm, but mainly to provide information about the aerosol extinction profiles and the corresponding lidar ratios at 532 nm. From the available correlative CALIOP level-2 and multiwavelength Raman lidar aerosol data over Athens, we selected to present cases that have been identified as Saharan dust outbreaks and large biomass burning events, using air mass backward trajectories in order to characterize the source of the aerosols. We found that the vertical profiles of the aerosol optical properties between CALIOP and NTUA lidars were not always in a good agreement during the exact time of the satellite overpass, especially for daytime measurements, when the distance between the two instruments was greater than 40 km. An improvement was noticed when ground-based lidar measurements where performed previously or later than the CALIPSO overpass time. For the nighttime intercomparison the agreement between the two instruments was better during the CALIPSO overpass time. This was attributed mainly to the closer nighttime satellite track over the Athens lidar station.
Keywords: Aerosols; Remote sensing; Optical radar; Backscattering